Meet the typographer - Bazin, Gaby, 1992- (New York City : David Zwirner Books, 2025)
"Enter the workshop, meet the typographer, and discover the world of letterpress printing. A follow-up to Meet the Lithographer, Meet the Typographer showcases the fascinating history, evolution, and technique of typography with colorful and engaging illustrations. Armed with little characters made of lead, a typographer reveals the secrets behind the fine art of letterpress printing. Gaby Bazin, in this new book, once again takes readers into the studio, unveiling the enchanting world of movable type. Following the mission of children's books from David Zwirner Books, this publication further illuminates the creative roles sometimes unknown in the art industry. This publication offers a distinct perspective on the printed medium"--